IL-19 suppresses Hippo signaling via modulating YAP1 phosphorylation in osteoarthritis - Deng, Jiezhong; Gu, Jun; Gong, Xiaoshan; Tang, Hao; Cai, Yuyi; Yang, Yusheng; Dong, Shiwu; Zhao, Chunrong (Frontiers in Immunology, 2025)
IntroductionOsteoarthritis (OA) is one of the most prevalent chronic degenerative diseases, characterized by the progressive destruction of joints, which is primarily evidenced by alterations in the phenotype of chondrocytes, chondrocyte apoptosis, and the progressive fibrosis of cartilage. Interleukin19 (IL-19) is predominantly expressed and secreted by B cells, monocytes, and macrophages. Recent studies have demonstrated that IL-19 attenuated inflammatory responses and facilitated tissue repair. However, no reported studies have explored the effects of IL-19 on osteoarthritis.MethodWe established an Interleukin 1β (IL-1β)-induced inflammation model and an anterior cruciate ligament transection (ACLT)-induced osteoarthritis model to validate the anti-inflammatory, anti-apoptotic, and osteoarthritis-delaying effects of IL-19.ResultsThis study found an elevated expression of IL-19 in the joints of OA mice and confirmed that the IL-19 in these joints primarily derives from synovial M2 macrophages. Additionally, we found that IL-19 mitigates IL-1β-induced osteoarthritis by inhibiting the Hippo signaling pathway and the phosphorylation of the YAP1 (Yes-associated protein 1) protein.ConclusionIL-19 represses the inflammatory response and apoptosis of IL-1βw-induced chondrocytes, thereby helping to delay the progression of osteoarthritis.